Data for 3D printing enlarged museum specimens for the visually impaired - Plessis, Anton; Els, Johan; Roux, Stephan; Tshibalanganda, Muofhe; Pretorius, Toni (My University, 2020)
Museums are embracing new technologies and one of these is the use of 3D printing. 3D printing allows for creating physical replicas of items which may, due to great value or significance, not be handled by the public, or which are too small or fragile to be handled or even seen with the naked eye. One such application of new technologies has been welcomed by the National Museum in Bloemfontein, Free Sate, South Africa. Here, blown-up (enlarged) Museum specimens were 3D printed for various interactive exhibits that are aimed at increasing the accessibility of their permanent displays for visually impaired visitors who rely greatly on touch as a source of observation. A selection of scorpions, pseudoscorpions, mites and archetypal bird skulls were scanned, processed and 3D printed to produce enlarged, highly functional nylon models. This data paper provides the raw micro Computed Tomography (micro-CT) scan data and print ready STL files processed from this data. The STL files may be used in their current format and details of the printing are provided.
Keywords: Imaging; microCT; Museum Collections